Heading machine pose detection system and method based on V-shaped laser target image recognition - DONG HAIBO; LIANG HONGYUAN; TAN YU; XU JIYUAN (2020)
The invention discloses a heading machine pose detection system and method based on V-shaped laser target image recognition. The system comprises a cross-shaped laser orientation instrument, a semi-transparent V-shaped laser target, a digital camera, an image processing computer and a dust cover. The semi-transparent V-shaped laser target is mounted on a heading machine; a cross-shaped laser imageis formed on the target by utilizing laser emitted by the cross-shaped laser orientation instrument fixedly mounted in a roadway; the digital camera behind the target collects the laser image on thetarget; the image processing computer is used for completing image recognition and processing; by using an established heading machine resolving pose model and adopting a space coordinate resolving method, the roll angle, the pitch angle, the deviation angle and the gravity center deviation parameter of the heading machine are obtained. The system and the method can be used for position deviationrectification in the headin